PENGARUH KUALITAS BARANG TERHADAP KEPUASAN PELANGGAN DENGAN PEMBELIAN MENGGUNAKAN APLIKASI SHOPEE - Dina Alfajrin; Doni Putra Utama (Program Studi Akuntansi, 2022)
The purpose of this study is to determine the influence of the quality of goods on purchasing decisions. Quantitative research is the type of this study, and the population is the people of Batam City, while the research sample is a total of 100 respondents. Researchers use non-probability sampling techniques. Questionnaires are used in data collection. For data analysis, use classical assumption test, reablity test, validity test, and descriptive statistical analysis. The research resulted in a relatively high category of quality goods in Shopee as seen from consumers who want to repurchase and are recommended to others.